Seeds Oils of the Most Consumed Cucurbitaceae Benin: Phytochemistry and Antimicrobial Activities - Koukpemedji E. W., E. W.; BOTHON, FIFA THEOMAINE DIANE; BOGNINOU AGBIDINOUKOUN, G. SOPHIE REINE; AGBANGNAN, DOSSA COKOU PASCAL; YETE, PELAGIE; WOTTO, VALENTIN DIEUDONNÉ; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2018)
Citrullus lanatus, Cucumeropsis edulis and Lagenaria siceraria are three species of squash widely cultivated and used in food in Benin. The aim of this study is to determinate the physicochemical characteristic and antimicrobial activities of their seeds oil. Oils were obtained by Soxhlet extraction; their quality index were evaluated according to the methods listed in the „‟AFNOR‟. The oil yield of the seeds of the three cucurbits ranged from 36.23 to 42.28%, the moisture contents of the seeds oils ranged from 0.47 and 0.98%. In terms of quality index, the values are between: 5.04-14.58 mg/g for acid value, 31.70 - 31.86 % for iodine, 1.65 - 8.42 meqO2/Kg-oil for peroxide value, 50.49 - 75.73 mg KOH/g-oil saponification and for ester 40.39 - 70.68%. Their calculated calorific value varies between 44611.05 and 45717.65 Kj /Kg-oil). AAS revealed that these oils had low content of Iron, Manganese and Potassium and do not contain Sodium at all. HPLC showed that the three oils are good sources of fat-soluble vitamins (A, E and K1) with 6.18 mg/100g vitamin E in Citrullus lanatus seeds oil and K1 (0.83 mg / 100g). They were all bacteriostatic and fungistatic on the strains explored but Citrullus lanatus and Cucumeropsis edulis oils had an antibiotic power on Escherichia coli and Staphylococcus aureus.
Keywords: Squashes; Oils; Physico-Chemistry; Antimicrobial Power